2021
DOI: 10.3126/medphoenix.v6i1.36823
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dry Eye Symptoms in Health Workers of National Medical College and Teaching Hospital following Corona Virus Pandemic

Abstract: Background: With the outspread of global pandemic Corona virus disease 19. (COVID-19), use of face masks was taken as a vital deed against severe acute respiratory syndrome coronavirus-2. (SARS-CoV-2) The aim of this study was to assess symptoms of mask associated dry eye (MADE) among health workers. Materials and Methods:   A total of 169 heath workers meeting the inclusion criteria were selected by simple random sampling from respective department. Data were obtained by providing with questionnaire est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 22 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Bista et al suggested that the increased use of gadgets caused the increased incidence of dry eye during the pandemic because almost all work, teaching, and learning activities are carried out online using electronic devices. 16 The study by Inomata et al showed that exposure to screen gadgets for more than 8 hours per day was significantly associated with dry eye symptoms (p<0.001). The results of this study also provided a similar situation where prolonged use of gadgets had a risk of lowering TBUT, but it was not statistically significant.…”
Section: Original Articlementioning
confidence: 97%
See 1 more Smart Citation
“…Bista et al suggested that the increased use of gadgets caused the increased incidence of dry eye during the pandemic because almost all work, teaching, and learning activities are carried out online using electronic devices. 16 The study by Inomata et al showed that exposure to screen gadgets for more than 8 hours per day was significantly associated with dry eye symptoms (p<0.001). The results of this study also provided a similar situation where prolonged use of gadgets had a risk of lowering TBUT, but it was not statistically significant.…”
Section: Original Articlementioning
confidence: 97%
“…Several studies suggest using protective eyewear to maintain humidity in the air around the eyes while wearing a mask. 3,7, 16 Tomlinson et al suggested using eye drops, especially those containing sodium carmellose and lipid formulas simultaneously, to reduce tear evaporation. 22 This research is an analytical study using a cross-sectional method, which has several limitations that could potentially lead to biased outcomes, including the absence of a control group with a history of not wearing a mask, high variance with an unbalanced comparison of the number of samples between groups, the absence of only one examiner measuring TBUT, the lack of detailed data on how each type of mask affects the airflow coming out of the upper gap of the masks, as well as the possibility of a chronic condition in the tear film due to the process of the MADE mechanism, considering that regular use of masks has been mandatory since early 2020.…”
Section: Original Articlementioning
confidence: 99%
“…All studies were published between 2020 and 2022. Five studies were conducted in Asia 7,[9][10][11]15 and one study in Europe 8 . All of the studies were cross-sectional.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Despite assessing subjective symptoms of dry eye, several studies also used objective measures to assess signs of dry eye related to face mask use in their studies. [7][8][9][10][11] The duration of mask-wearing continued to be one of the interesting factors to look for regarding the incidence of mask-associated dry eye. A survey study found that there is no significant association between mask-wearing and symptomatic dry eye disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation